2021
DOI: 10.1002/lt.26312
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion After Coronavirus Disease 2019 Vaccination in Patients Awaiting Liver Transplantation: Fact or Fancy?

Abstract: Chronic liver disease increased the risk of severe coronavirus disease 2019 (COVID‐19). Trials to assess efficacy/safety of COVID‐19 vaccines in liver disease are underway. We evaluated the humoral immune response and safety of anti–COVID‐19 vaccination among patients waiting liver transplantation (LT). We enrolled all pre‐LT adults who completed anti‐COVID‐19 vaccination between January 2021‐August 2021 as study group. Patients with histories of COVID‐19 received 1 vaccine dose, and all others received 2 dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…In particular, data indicate that uremia associates with increased T cell exhaustion ( 28 ) and low response to vaccines ( 29 ), which could, at least partially, explain, the impaired serological responses to SARS-CoV-2 vaccines in kidney transplant recipients, as well as in patients with kidney failure ( 30 , 31 ). Consistent with this hypothesis, response to SARS-CoV-2 vaccine in patients with liver failure is not significantly impaired ( 32 ).…”
Section: Discussionmentioning
confidence: 72%
“…In particular, data indicate that uremia associates with increased T cell exhaustion ( 28 ) and low response to vaccines ( 29 ), which could, at least partially, explain, the impaired serological responses to SARS-CoV-2 vaccines in kidney transplant recipients, as well as in patients with kidney failure ( 30 , 31 ). Consistent with this hypothesis, response to SARS-CoV-2 vaccine in patients with liver failure is not significantly impaired ( 32 ).…”
Section: Discussionmentioning
confidence: 72%
“…In patients with non-alcoholic fatty liver disease (NAFLD), seropositivity rates of 95.5% were described [ 20 ]. In patients with liver cirrhosis, Thuluvath et al reported a seroconversion of 95.9% in a group of 79 patients with liver cirrhosis [ 21 ], and Calleri et al observed a seroconversion rate of 94.4% in 89 pre-transplant patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Únicamente se encontró un registro de un paciente trasplantado, lo que deja abierta la puerta a la investigación en este grupo de pacientes, quienes ya tienen un mayor riesgo de mortalidad por cualquier causa debido a que son pacientes inmunosuprimidos; sin embargo, esto refuerza el concepto de la protección con la inmunización ya que este grupo de pacientes tiene una menor respuesta inmunogénica (50 % aproximadamente), a diferencia de aquellos inmunocompetentes con respuestas cercanas al 94 % (18,19) .…”
Section: Discussionunclassified